Development of Teaching Material Modules Using The Guided Note Taking Method for Fiqh Learning Class VII at MTsN 12 Padang Panjang - Revi Junianti (Al Bahri: Journal of Islamic Education, 2024)
One of the objectives of this study is to determine the development of the material module using the Guided Note Taking method in class VII Fiqh learning at MTsN 12 Tanah Datar. The Guided Note Taking method is a lecture method developed by teachers using modules given to students in the form of blank points. Students will concentrate and pay attention to learning and students are expected to play an active role in expressing their opinions. This research is a development research with a 4-D model from Thiagarajan (Define, Design, Develop, Disseminate) but researchers have only reached the Development stage. This research was carried out at MTsN 12 Tanah Datar in the first semester of Fiqh class VII. The data collection techniques used were observation, interviews, documentation and validation questionnaires for material, language and media experts. A module is declared viable if it meets valid aspects. Validity is seen from the validation results using validation sheets. Based on the results of the study, the results of the material expert's assessment of the assessment of the Guided Note Taking aspect obtained an average result of 87 with the "Very valid" criterion, then the content feasibility aspect obtained 86 results with the "Very valid" criterion, then in the construction feasibility aspect (presentation component) 93 results were obtained with the "Very valid" criterion. The results of the linguist's research obtained an average score of 67 with the "valid" criterion. In the communicative aspect, 70 results were obtained with "valid" criteria. In the aspect of using terms, symbols and icons, 70 results were obtained with "valid" criteria and in the dialogical and interactive aspects, 80 results were obtained with "valid" criteria. The results of media research on aspects of presentation display design, validators gave an average of 78 with "valid" criteria. The suitability aspect of content produced an average of 65 with the "valid" criterion. The engineering aspect of writing obtained an average of 90 with the "valid" criterion.